Towards transdisciplinary and transformative coastal marine research: insights from Costa Rica - Sánchez-Jiménez, Astrid (2025)
Introduction: Transformative transdisciplinary research (TTDR) aims to address complex sustainability issues of our times by engaging researchers from different disciplines, practitioners, individuals, and policymakers. Objective: This literature review is a first structured effort to understand how marine-coastal research published in English and Spanish can drive transformative change towards sustainability in Costa Rica (n = 30 articles) and is expected to foster critical reflection on the role of scientific systems in the design, production, and use of knowledge. Results: The results show that in Costa Rica, knowledge production remains largely unidirectional, with stakeholder consultation prevailing over co-production. It highlights the need to foster collaborative research that includes historically underrepresented groups, such as women. Power and funding dynamics determine research priorities, with efforts concentrated in the North Pacific, while the Caribbean region remains underrepresented. Conclusions: Furthermore, we highlight ways forward to transformative research: a focus on leverage points such as co-production of knowledge, creation of safe spaces for inclusive dialogue, and reform of funding models to support long-term interdisciplinary collaboration. As Costa Rica will co-host the upcoming Ocean Conference in France, this moment presents an opportunity to align national research efforts with global transformative trends, ensuring that marine research evolves towards more inclusive and action-oriented frameworks.